DAMPAK DIVERSIFIKASI TERHADAP KINERJA PERUSAHAAN - Sulastri, Sulastri (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2008)
The economic theory scope informed that diversification is potential to create value. But some empirical study indicates in contrary. These findings are motivate the researcher to describe how the impact of diversffication to the firm's performance, are there any differences ofpre andpost diversification, and what are the differences of the performance on the diversification categories (dominant business, related, and unrelated business)The analysis is conducted to the event study data since 1990 until 2002, the samples are taken from 153 companies as the manufacture sector of go public companies listed on Jakarta Stock Exchange Indonesia. The model tested empirically, to find the different of before and after diversification, through the analysis of variance, and paired related sample.Statistically tested concludes there are performance differences before and after diversification, and diversification did not create the value especially on unrelated business diversification.